Health value & perceived control over health: behavioural constructs to support Type 2 diabetes self‐management in clinical practice. Issue 15 (28th May 2015) - Nugent, Linda Elizabeth; Carson, Maggie; Zammitt, Nicola Naomi; Smith, Graeme Drummond; Wallston, Kenneth A
<x xml:space="preserve">Abstract</x> Aims and objectives To explore health value and perceived control over health in relation to self‐management behaviours in adults with Type 2 diabetes mellitus. Background Helping people to modify health related behaviour in diabetes is complex due to a multitude of factors. Exploring the meaning of the constructs of Modified Social Learning Theory could be beneficial to identifying people at risk of poor diabetes self‐management. Design An exploratory qualitative study. Methods Thirteen adults with insulin‐treated Type 2 diabetes mellitus were purposively sampled. Data were collected through semi‐structured interviews. An in‐depth thematic analysis was carried out. Results Health became a value priority on diagnosis of Type 2 diabetes mellitus. Participants described holding both terminal (relating to desired end states) and instrumental (a means to an end) health values pre‐diagnosis but these became instrumental post‐diagnosis to meet new lifestyle needs and maintain their quality of life. Descriptions of 'conflicts' in locus of control beliefs when managing Type 2 diabetes mellitus demonstrated influences on levels of self‐efficacy and health value. Common themes that impacted on diabetes self‐management included co‐morbidities, medication management, blood glucose monitoring and reasoning for Type 2 diabetes mellitus. Conclusions Locus of control beliefs, levels of self‐efficacy and health value were influenced by complications associated with Type 2 diabetes mellitus. The findings on Modified Social Learning Theory and instrumental health value as a moderator to health behaviour resulted in the development of a proposed framework with potential practical utility. Relevance to clinical practice This research demonstrates the relevance of exploring the constructs of Modified Social Learning Theory (MSLT) in relation to diabetes self‐management behaviours in Type 2 diabetes mellitus. The proposed Type 2 diabetes mellitus Self‐management Behaviour Support framework incorporates Modified Social Learning Theory and instrumental health value as the theoretical basis for development and could provide clinical nurses and doctors with a tool that will allow for in‐depth assessment and planning of Type 2 diabetes mellitus patients' self‐management behaviours.